A mixed-methods study of the disease experience in hematopoietic stem cell transplantation survivors: the contribution of text analysis. Issue 6 (9th September 2020) - Sinatora, Francesco; Di Florio, Nicoletta; Traverso, Annalisa; Zanato, Silvia; Porreca, Alessio; Tremolada, Marta; Tumino, Manuela; Marzollo, Antonio; Mainardi, Chiara; Gabelli, Maria; Calore, Elisabetta; Pillon, Marta; et al.
Abstract: Objectives: Few studies have detected qualitative and quantitative aspects of patients who underwent HSCT during childhood. The aims of this study are to explore the most recurrent narrative themes of HSCT experience in families five years after the procedure, and to observe statistical correlations between meaning attributed to the experience and defined variables. Methods: Thirty-five families of pediatric HSCT survivors participated in the research. Both survivors and their families were asked to write a brief composition about their disease experiences. Qualitative analysis of the texts was performed using the T-LAB software. Information about medical aspects and psychological problems in HSCT survivors were collected with interviews and administering the Child Behavior Checklist 6–18. Results: HSCT survivor families that reported the presence of externalizing and internalizing symptoms focused on thematic areas concerning broken families with separation between parents and the affected child versus healthy children. Conclusions: Long term psychological problems seem to be connected to the perception of family disruption. Specifically, family relationships seem to be the factor that protects from or enhances the risk of psychopathology in HSCT survivors. Moreover, the use of metaphoric terms to refer to HSCT presents higher associations with psychopathology. On the contrary, the possibility of referring directly to the transplantation is associated with psychological well-being. It is important to consider the family as a group in order to improve care.